Graded prime spectrum of a graded module - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
Let R be a graded ring and M be a graded R -module. We define a topology on graded prime spectrum G - Spec(M) of the graded R -module M which is analogous to that for G - Spec(R), and investigate several properties of the topology.
Keywords: Graded module; graded prime spectrum; graded prime submodule